Glyco engineered pentameric SARS-CoV-2 IgMs show superior activities compared to IgG1 orthologues - Kallolimath, Somanath; Palt, Roman; Föderl-Höbenreich, Esther; Sun, Lin; Chen, Qiang; Pruckner, Florian; Eidenberger, Lukas; Strasser, Richard; Zatloukal, Kurt; Steinkellner, Herta (Frontiers in Immunology, 2023)
Immunoglobulin M (IgM) is the largest antibody isotype with unique features like extensive glycosylation and oligomerization. Major hurdles in characterizing its properties are difficulties in the production of well-defined multimers. Here we report the expression of two SARS-CoV-2 neutralizing monoclonal antibodies in glycoengineered plants. Isotype switch from IgG1 to IgM resulted in the production of IgMs, composed of 21 human protein subunits correctly assembled into pentamers. All four recombinant monoclonal antibodies carried a highly reproducible human-type N-glycosylation profile, with a single dominant N-glycan species at each glycosite. Both pentameric IgMs exhibited increased antigen binding and virus neutralization potency, up to 390-fold, compared to the parental IgG1. Collectively, the results may impact on the future design of vaccines, diagnostics and antibody-based therapies and emphasize the versatile use of plants for the expression of highly complex human proteins with targeted posttranslational modifications.